Comparing traditional and commercial nixtamalization of three maize landraces: Impact on pozole quality and consumer acceptance - Vazquez-Carrillo, María Gricelda; Hernández-Montes, Arturo; Palacios-Rojas, Natalia; Garcia-Cruz, Leticia; Rosales-Nolasco, Aldo; Molina Macedo, Aide; Palacios-Pola, Gabriela (BioMed Central, 2024)
One of the most typical dishes of traditional Mexican cuisine is pozole, made with nixtamalized maize. This dish has a special place as part of the identity of Mexican culture. However, it is time-consuming to prepare. With an increasing demand for precooked maize for pozole and the limited information on its preparation process, this study aims to assess the impact of both traditional (TN) and commercial nixtamalization (CN) on the quality of processed maize and its reception by consumers, focusing on the three most popular maize landraces used in pozole recipes. This study was carried out with the Cacahuacintle (‘CAC’), Elotes Occidentales (‘EO’) and Ancho (‘AN’) landraces, which were nixtamalized using the traditional method (only lime) and the commercial method (lime + additives) and the grain was flowered. The quality of the flowered grain was determined, and a sensory analysis consisting of magnitude of difference tests, a descriptive analysis, affective test and evaluation of consumer preferences was carried out. The ‘CAC’ landrace, when processed traditionally, yielded the highest sensory and commercial quality. The ‘EO’ landrace demanded a longer flowering time, resulting in less volume but retaining the aleurone layer. This characteristic helped preserved a portion of the anthocyanins. Consistently, maize landraces subjected to traditional nixtamalization displayed higher ratings for attributes related to masa and nejayote aroma. The ‘CAC’ landrace subjected to CN faced challenges in acceptability due to odors of acetic acid and sulfuric acid. These findings underscore the importance and advantages the TN techniques. They also emphasize the need to preserve grain quality and meeting consumer preferences when exploring alternative maize processing methods for emerging markets.